2005
DOI: 10.1007/s10541-005-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis of Human Red Blood Cells by Riboflavin-Cu(II) System: Enhancement by Azide

Abstract: Photoactivated riboflavin in the presence of Cu(II) generates reactive oxygen species (ROS) which can hemolyze human red blood cells (RBC). In the present work we examined the effect of sodium azide (NaN3) on RBC in the presence of riboflavin and Cu(II). The addition of NaN3 to the riboflavin-Cu(II) system enhanced K+ loss and hemolysis. The extent of K+ loss and hemolysis were time and concentration dependent. Bathocuproine, a Cu(I)-sequestering agent, inhibited the hemolysis completely. Among various free ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…. Ali et al 58 reported that the hemolysis of human red blood cells by a photoactivated (cool fluorescent light) riboflavin–Cu(II) system was enhanced by addition of 150 µM azide. They attributed their observation to inhibition of the photodegradation of riboflavin, but commented that “as the riboflavin–Cu(II) system has been shown to produce HO .…”
Section: Discussionmentioning
confidence: 99%
“…. Ali et al 58 reported that the hemolysis of human red blood cells by a photoactivated (cool fluorescent light) riboflavin–Cu(II) system was enhanced by addition of 150 µM azide. They attributed their observation to inhibition of the photodegradation of riboflavin, but commented that “as the riboflavin–Cu(II) system has been shown to produce HO .…”
Section: Discussionmentioning
confidence: 99%
“…Land and Prutz [62] found that addition of 10 mM azide potentiated the inactivation of enzymes by pulse radiolysis and attributed the finding to production of N3 from HO • . Ali et al [63] reported that the hemolysis of human red blood cells by a photoactivated (cool fluorescent light) riboflavin–Cu(II) system was enhanced by addition of 150 μM azide. They attributed their observation to inhibition of the photodegradation of riboflavin, but commented that “as the riboflavin–Cu(II) system has been shown to produce HO • the intermediacy of N3 • could not be ruled out.”…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the mechanism through which riboflavin biosynthesis boosts hemolysis is not clear. Riboflavin has been shown to direct light-mediated rat and human erythrocytes hemolysis but only in the presence of other factors such as serum, oxygen, copper, azide, and aminophylline ( Suzuki et al, 1982 ; Ali and Naseem, 2002 ; Ali et al, 2005 ). Moreover, riboflavin alone does not directly promote hemolysis in agar plates were H. pylori experiments were conducted ( Bereswill et al, 1998 ).…”
Section: Riboflavin Production As a Mean To Increase Iron Availabilitmentioning
confidence: 99%